EFFECT OF MANUAL THERAPY TECHNIQUES AND PAIN ON RANGE OF MOTION IN THE CERVICAL REGION ABSTRACT (Fiep Bulletin - online, 2012)
Neck pain is a common disorder and affects approximately two thirds of the population. The muscles of the neck have the function of balancing the head and suspend the thoracic spine and shoulder girdle. As a result, imbalances occur, shortening, contractures and painful downturns, however, in many cases it is not possible to detect its cause. The techniques provide mechanical and muscle reflexes. The responses of the central nervous system techniques also include muscle pain relief and muscle relaxation, caused by changes in the function of the drive motor and sensory receptors similar to Golgi tendon organs and muscle spindle. In this sense, the aimed of this study is to verify the effect of 10 sessions of manual therapy for the treatment of neck pain, with regard to pain relief and increased range of motion in young adults. For this purpose, the methodology consisted of a sample of ten female patients aged between 34 and 53 years, complaining of neck pain or discomfort, which were treated with technical manual cervical traction, stretching bilateral sternocleidomastoid, scalene, levator scapulae, upper trapezius, middle trapezius and lower trapezius, technical release trigger points and mobilization of the cervical segment. In the first and last visit were assessed range of motion of the cervical region, and during all sessions was noted, at the beginning and the end of the intervention, the degree of pain reported by patients. The results were significant, both in terms of decreased pain and increased range of motion. From this study it was concluded that manual therapy is effective to decrease pain and increase range of movement of young adults who have any pain or discomfort nonspecific cervical origin.
Keywords: neck pain; manual therapy; range of motion